Cross layer design for video transmission over wireless network using H.264/AVC - Suleiman Baguda, Yakubu (2007)
International Conference on Robotics, Vision, Signal Processing & Power Applications (ROVISP) is organized by School of Electrical and Electronic Engineering, Universiti Sains Malaysia. ROVISP 2016 welcomes researchers, scientists, engineers, academicians as well as industrial professionals from all around the globe to present their research results and development activities for oral or poster presentations.